# 1/4x-6=1/3x

## Simple and best practice solution for 1/4x-6=1/3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 1/4x-6=1/3x equation:

1/4x-6=1/3x
We move all terms to the left:
1/4x-6-(1/3x)=0

Domain of the equation: 4x!=0
x!=0/4
x!=0
x∈R

Domain of the equation: 3x)!=0
x!=0/1
x!=0
x∈R

We add all the numbers together, and all the variables
1/4x-(+1/3x)-6=0
We get rid of parentheses
1/4x-1/3x-6=0
We calculate fractions

3x/12x^2+(-4x)/12x^2-6=0
We multiply all the terms by the denominator

3x+(-4x)-6*12x^2=0
Wy multiply elements
-72x^2+3x+(-4x)=0
We get rid of parentheses
-72x^2+3x-4x=0
We add all the numbers together, and all the variables
-72x^2-1x=0
a = -72; b = -1; c = 0;Δ = b2-4acΔ = -12-4·(-72)·0Δ = 1The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1}=1$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-1}{2*-72}=\frac{0}{-144} =0$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+1}{2*-72}=\frac{2}{-144} =-1/72$

`